2006
DOI: 10.1111/j.1440-1746.2006.04183.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of minocycline‐based triple therapy for eradication of Helicobacter pylori infection

Abstract: A combination of rabeprazole, minocycline, and metronidazole is safe and effective for second-line therapy of H. pylori infection. Because this regimen can be administered to patients with penicillin allergy and patients who suffer adverse reactions to amoxicillin, such as diarrhea and other digestive symptoms, it should be considered useful for second- and third-line eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…shows a disappointing e ectiveness (38.5%) [13]. However, the case of a multi-resistant H. pylori strain successfully treated with minocycline/amoxicillin/bismuth has been described [14].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on the use of faropenem in antimicrobial therapy for H. pylori have been published [22,23]. Togawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data demonstrated that faropenem has a very low minimum inhibitory concentration (MIC) against H. pylori [21]. Two eradication studies with faropenem have been performed, but they found widely differing eradication rates of 91.3 and 9.5%[22,23]. We report the MIC of faropenem against 78 clinical H. pylori isolates from Japanese.…”
mentioning
confidence: 98%